Comparison of cytokine/chemokine levels in aqueous humor of primary open-angle glaucoma patients with positive or negative outcome following trabeculectomy - Gajda-Deryło, Beata; Stahnke, Thomas; Struckmann, Stephan; Warsow, Gregor; Birke, Kerstin; Birke, Marco T.; Hohberger, Bettina; Rejdak, Robert; Fuellen, Georg; Jünemann, Anselm G. (Bioscience Reports, 2019)
We aimed to identify differences in cytokine/chemokine levels in the aqueous humor (AH) of primary open-angle glaucoma (POAG) patients who suffered from scarring, compared with POAG patients with no scarring after trabeculectomy surgery. Identification of differently expressed cytokines and chemokines may help to understand scarring and fibrotic processes following trabeculectomy, and to make predictions for the outcome of fistulating surgery in the future. Furthermore, the identification of cell signaling pathways involved in fibrosis offers the opportunity for a more specific antifibrotic therapy with reduced side effects, and an improvement in long-term surgical outcome.Eight samples of AH were collected during trabeculectomy surgery and commercially available cytokine/chemokine arrays were used. Specific, differently expressed proteins (cytokines/chemokines) in AH samples from patients with positive and negative surgery outcomes were detected. These proteins were classified based on their known profibrotic, inflammatory, adhesive, and apoptotic properties. Transforming growth factor β (TGF-β) and vascular endothelial growth factor (VEGF) were among the most important profibrotic cytokines that we detected. Differences in the fold change of protein expression were highly significant between patients after successful and failed trabeculectomy surgery, and these were processed and visualized using ExprEssence software.This pilot study revealed differences in concentrations of cytokines/chemokines in AH between the two examined groups of patients. Our findings suggest that a positive outcome from trabeculectomy is strongly related to an inhibition of the fibrosis process.
CRIS-Team Scopus Importer:2019-05-21
Keywords: bioinformatics; ophthalmology; protein expression